Carok as Self-Esteem: Korsa in the Philosophy and Ethics of Nusantara Culture - Harry Yulianto (Jurnal Sosial Humaniora dan Pendidikan, 2026)
Carok is examined as a manifestation of self-esteem in Madurese society through the lens of Nusantara cultural philosophy and ethics, with particular focus on the value of korsa (courage). A qualitative descriptive design based on literature study was employed by analyzing scholarly texts on Madurese tradition, cultural philosophy, and Nusantara ethical systems. Hermeneutic interpretation indicates that korsa is not merely physical bravery but a structured moral force that integrates self-esteem (ajhâr) and shame (lebbher) within a relational ethical system. Within this framework, korsa operates as an ethical response activated when honor is threatened and conventional mechanisms of restoration are no longer effective. Carok emerges as the most extreme expression of korsa when restorative pathways fail to reestablish social dignity, showing that violence is culturally constructed as a last moral resort rather than irrational action. The findings demonstrate that the logic of carok is coherent within Madurese ethical reasoning, while contrasting sharply with state legal ethics that prioritize universal non-violence principles. Therefore, conflict prevention policies need to transform korsa into constructive forms of expression without erasing its cultural and philosophical foundations.